IMPLEMENTASI KONSTANTA ABCD PADA SALURAN TRANSMISI 150KV BERBASIS ICT - Debi Rahmadani; Helmi Alfianza; Hasan Yanmar Lubis; Feby G Telaumbanua; Ivan Aditya Pasaribu; Ricco Perangin-Angin; Agus Junaidi (Jurnal Publikasi Teknik Informatika, 2026)
Modern power systems rely on high-voltage transmission lines as the primary means of delivering energy from generating stations to load centers. In Indonesia, the 150 kV network serves as the backbone of regional interconnection, making accurate analysis essential to maintain voltage quality and minimize power losses. This study aims to analyze the performance of the 150 kV Payapasir–Mabar transmission line using the ABCD parameter approach based on the nominal-π model. The methodology involves calculating ABCD constants from technical line data and validating the results with real-time operational data obtained from the Information and Communication Technology (ICT) system. Two operating conditions are selected as case studies: normal load (07:00 WIB) and peak load (19:00 WIB). The results indicate that constants A and D are close to unity, reflecting system stability. Under normal load, GIS 1 delivered 34.82 MW with an efficiency of 97.6% and a voltage regulation of 0.79%, while GIS 2 achieved 97.38% efficiency with 0.52% regulation. At peak load, voltage regulation increased to 1.24% for GIS 1 and 1.22% for GIS 2, yet efficiency remained high at above 97.3%. The findings demonstrate that the ABCD parameters can serve not only as a theoretical framework but also as a predictive analysis tool to evaluate line performance, support dynamic monitoring, and facilitate rapid decision-making in maintaining the reliability of the 150 kV transmission network.